TL response of LiF:Mg, Cu, P (GR200A and GR207A) exposed to high-energy 12C ions. (July 2015) - Zhang, X.Y.; Chen, L.; Luo, P.; Ju, Y.Q.; Zhang, H.B.; Ma, F.; Ge, H.L.; Zhang, Y.B.; Wan, B.; Li, Y.Y.; Xu, X.W.; Mao, W.
Abstract: The characteristics of nat ., 7 LiF:Mg, Cu, P thermoluminescent detectors exposed to high-energy 12 C (165 MeV/nucleon) ions and 60 Co γ -rays have been investigated. Through a careful analysis of the glow curves by the GlowFit program, it is found that the relative amplitude of satellite peaks 3, 5, 6 and 7 to peak 4, measured after irradiated with high-energy 12 C ions, is higher than that with 60 Co γ -rays for both types of TL detectors. It is observed that nat ., 7 LiF:Mg, Cu, P thermoluminescent detectors would also exhibit a good linear dose response when the delivered dose of high-energy 12 C ions is in the range from 100 mGy to 1600 mGy. Furthermore, the relative efficiency of the nat ., 7 LiF:Mg, Cu, P thermoluminescent detectors is independent of the absorbed dose in the linear dose response range. Compared to previously published data, the relative efficiency of the 7 LiF:Mg, Cu, P TL detectors decreases with increasing LET values. Highlights: GR200A and GR207A detectors exposed to high-energy 12 C ions are studied. Glow curves induced by high-energy 12 C ions and 60 Co γ-rays are different. Good linear dose response of GR200A and GR207A detectors are observed. Relative TL efficiency of LiF:Mg, Cu, P are independent of the absorbed dose. Efficiency of GR207A detector decreases with increasing LET values.